TV-serien SKAMs byforestillinger - Innenfor og utenfor det urbane - Riesto, Svava; Steiner, Henriette (Nordisk Tidsskrift for Informationsvidenskab og Kulturformidling, 2017)
This article discusses the understanding of urbanity invoked by the Norwegian drama series SKAM. It does so by revisiting the four short preambles to each of the series’ four seasons, thus outlining the central narratives used to frame each season. Norwegian culture is characterised by a long-lived tradition for valuing nature and life in the countryside over and above urban life. In this context, SKAM arguably appears as a sea change, using new media and narrative forms to aestheticize the life of a new generation of teenagers in Oslo. However, this article’s close reading of selected sequences of the series illuminates SKAM’s indebtedness to an anti-urban tradition. According to this tradition, the city centre is seen as dark and dangerous and full of corrupting temptations, and, in contrast, what lies outside the city is regarded as authentic, liberating and morally superior. What is at stake is a dual-sided evaluation of city and countryside – building on binaries such as genuine vs. superficial - which may be seen to mirror human emotions, ethical concerns and affects. In this way, SKAM becomes a vehicle for recirculating dual-sided understandings of the urban condition, which become evaluated according to well-known criteria.